Pragmatics Analysis of Intentions and Motives of Hate Speech on Hailey Bieber's Instagram - Pebrianti, Anggi; Rosita, Nur (Universitas Negeri Padang, 2024)
Pragmatics analysis and hate speech are closely related in which hate speech is analyzed based on the context between speakers and hearers that affect communication, so the message conveyed by the speaker contains the meaning of action in accordance with the context. Hate speech is an action or utterance that crosses the line and causes a negative impact. The aims of this research are to analyze intentions of hate speech and motives of hate speech which mostly used by netizens in Hailey Bieber’s Instagram comment section. The data of this research were utterances from netizens in the comment section of one post on 2 November 2023 Hailey Bieber’s Instagram. This research used theory by Kreidler (2002) to analyze intentions and also theory by Pinker (2011) to analyze motives of hate speech in one post of Hailey Bieber’s Instagram comment section. This research was a descriptive qualitative method. From 220 data, it was found that there were five intentions of hate speech, namely mocking, accusing, blaming, insulting, and insinuating. Also, five motives of hate speech namely instrumental violence, dominance, revenge, ideology, and sadism. Insinuating was mostly found for intentions of hate speech and sadism was mostly found for motives of hate speech used by netizens on Hailey Bieber’s Instagram. This research found that netizens tend to deliver hate speech comments against the celebrity explicitly.